Topic Modeling and Sentimental Analysis of Tweets on Covid19 to Find the Weightage of the Popular Hashtag (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Hashtags plays a vital role in the social media and it is easily highlighted by each and every people when they tag it for their own views. Marketing and advertisement is booming so that to make their products work through the views of the normal or common people. Sometimes they use the false content for their publicity and misleading the people. In this paper, the covid19 tweets are taken for finding out the popular hashtags using the correlation techniques like pearson, spearman and kendall rank correlation. The Covid19 hashtag is more popular with the correlation coefficient and sentimental analysis of the tweet than coronovirus tag. To justify the popularity, the weightage’s of the hashtag is found out by applying the topic modeling. In that the coronovirus tag is having more weightage than Covid19 tag.